2006
DOI: 10.1051/0004-6361:20066078
|View full text |Cite
|
Sign up to set email alerts
|

An optimal hydrodynamic model for the normal type IIP supernova 1999em

Abstract: Context. There is still no consensus about progenitor masses of type IIP supernovae. Aims. We study a normal type IIP SN 1999em in detail and compare it to a peculiar type IIP SN 1987A. Methods. We computed the hydrodynamic and time-dependent atmosphere models interpreting simultaneously both the photometric and spectroscopic observations. Results. The bolometric light curve of SN 1999em and the spectral evolution of its Hα line are consistent with a presupernova radius of 500 ± 200 R , an ejecta mass of 19.0 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
189
1
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(217 citation statements)
references
References 41 publications
20
189
1
7
Order By: Relevance
“…These steep density distributions in the SN ejecta are also predicted by numerical simulations (e.g. Chugai et al 2007;Utrobin 2007). We computed symmetric grids for the density distribution with 10 grid points on each axis, but for comparison we also produced models with higher resolution grids using 15, 30 and 49 grid points.…”
Section: Numerical Modelsmentioning
confidence: 66%
“…These steep density distributions in the SN ejecta are also predicted by numerical simulations (e.g. Chugai et al 2007;Utrobin 2007). We computed symmetric grids for the density distribution with 10 grid points on each axis, but for comparison we also produced models with higher resolution grids using 15, 30 and 49 grid points.…”
Section: Numerical Modelsmentioning
confidence: 66%
“…Utrobin (2007) found that both this one-group approach and the multi-group approach of Baklanov et al (2005) measured similar ejecta mass and explosion energy for SN 1999em. The basic equations and details of the input physics, including calculations of mean opacities, are described in Utrobin (2004).…”
Section: Model Overviewmentioning
confidence: 81%
“…At present, we can only state firmly that the multi-group treatment of radiation transfer cannot notably change the inferred SN parameters. This conclusion is based on the comparison between the multigroup (Baklanov et al 2005) and one-group (Utrobin 2007) approaches to the SN 1999em modeling. A major drawback of our model may be its one-dimensional approximation.…”
Section: Could Explosion Asymmetry Be a Crucial Missing Factor?mentioning
confidence: 99%
“…Radiation hydrodynamic calculations of the explosion and evolution of Type II SNe have been presented by Grassberg et al (1971), Falk & Arnett (1977), Falk (1978), Klein & Chevalier (1978), Hillebrandt & Müller (1981), and Litvinova & Nadezhin (1983, 1985, as well as more specifically for SNe II-P by Young (2004), Utrobin (2007), Utrobin & Chugai (2009), Bersten et al (2011), and Dessart & Hillier (2011), for SNe II-L by Swartz et al (1991) and Blinnikov & Bartunov (1993) and for the peculiar Type II-P SN 1987A by Blinnikov et al (2000), Dessart & Hillier (2010) and Pumo & Zampieri (2011). Here we give a summary view of the physical processes at play and the various evolutionary stages seen in these simulations.…”
Section: Appendix A: Light Curve Modelsmentioning
confidence: 99%